Excel maths early skills book 7: learning numbers to 20 - Dunbar, Bev (Oxford University Press Karachi, 2006)
"Excel Maths Early Skills Book 7: Learning Numbers to 20" helps young children understand and recognize numbers up to 20 through fun activities and visual aids. It emphasizes counting, number formation, and simple mathematical concepts to build a solid foundation in early numeracy.